2023
DOI: 10.1038/s41378-023-00518-y
|View full text |Cite
|
Sign up to set email alerts
|

A miniaturized transit-time ultrasonic flowmeter based on ScAlN piezoelectric micromachined ultrasonic transducers for small-diameter applications

Abstract: Transit-time ultrasonic flowmeters (TTUFs) are among the most widely used devices for flow measurements. However, traditional TTUFs are usually based on a bulk piezoelectric transducer, which limits their application in small-diameter channels. In this paper, we developed a miniaturized TTUF based on scandium-doped aluminum nitride (ScAlN) piezoelectric micromachined ultrasonic transducers (PMUTs). The proposed TTUF contains two PMUT-based transceivers and a π-type channel. The PMUTs contain 13 × 13 square cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 49 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…When immersed in deionized water, the resonant frequency of the PMUT decreased to 1.2206 MHz, and the −3 dB bandwidth expanded to 33.84 kHz, because of the mass loading effect [19]. The in-water −3 dB bandwidth of the PMUTs prepared in this paper is larger than that (20.3 kHz) in previous work [10]. The quality factor (Q) of the PMUTs is defined by the following Equation (3):…”
Section: Pmut Model Fabrication and Characterizationmentioning
confidence: 86%
See 1 more Smart Citation
“…When immersed in deionized water, the resonant frequency of the PMUT decreased to 1.2206 MHz, and the −3 dB bandwidth expanded to 33.84 kHz, because of the mass loading effect [19]. The in-water −3 dB bandwidth of the PMUTs prepared in this paper is larger than that (20.3 kHz) in previous work [10]. The quality factor (Q) of the PMUTs is defined by the following Equation (3):…”
Section: Pmut Model Fabrication and Characterizationmentioning
confidence: 86%
“…Moreover, both AlScN and AlN are CMOS compatible, which is more convenient in integration with circuits toward miniaturization [ 4 ]. PMUTs have many applications in the gas and fluid domains: in-air range detection [ 5 , 6 ], MEMS hydrophone [ 7 ], underwater communication [ 8 ], underwater wireless power supply [ 9 ], ultrasonic flowmeter [ 10 ], Doppler blood flowmeter [ 11 ], and fingerprint sensor [ 12 , 13 , 14 ]. Several studies on utilizing PMUTs for solid internal inspection have been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…The PMUT array in this paper utilizes a square structure, resulting in a higher fill rate of up to 81%. This allows more PMUTs to be placed in parallel within a limited space, resulting in high output power density and higher receiving sensitivity [25]. The PMUT array has an area of 2.8 mm × 2.8 mm, a cell spacing of approximately 200 µm, and 13 × 13 square elements.…”
Section: Structure and Simulation Of Pmutsmentioning
confidence: 99%
“…Besides, Liwei Lin's group proposed a flowmeter based on ultrasonic beams deflection in liquid flow, which allowed for both flow direction and velocity measurements of fluid using a single PMUTs chip [18]. Gao et al reported a miniaturized transittime flowmeter based on ScAlN PMUTs, which was capable of measuring flow rate in a 4 mm pipeline with an accuracy and repeatability of 0.2% and 1% respectively [19]. Utilization of a new flow channel design has the potential to enhance the propagation path of ultrasonic waves within the fluid, while a dual-channel design may reduce random measurement errors [20].…”
Section: Introductionmentioning
confidence: 99%